2016
DOI: 10.1371/journal.pone.0158525
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of In Vivo-Expressed HIV-1 Spliced RNAs Reveals the Usage of New and Unusual Splice Sites by Viruses of Different Subtypes

Abstract: HIV-1 RNAs are generated through a complex splicing mechanism, resulting in a great diversity of transcripts, which are classified in three major categories: unspliced, singly spliced (SS), and doubly spliced (DS). Knowledge on HIV-1 RNA splicing in vivo and by non-subtype B viruses is scarce. Here we analyze HIV-1 RNA splice site usage in CD4+CD25+ lymphocytes from HIV-1-infected individuals through pyrosequencing. HIV-1 DS and SS RNAs were amplified by RT-PCR in 19 and 12 samples, respectively. 13,108 sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 76 publications
0
14
1
Order By: Relevance
“…In addition to the canonical splice sites, several studies have reported the presence of alternative or cryptic splice sites in different clades of HIV-1 group M (Purcell and Martin, 1993; Ocwieja et al, 2012; Vega et al, 2016). While some of these sites are conserved among diverse HIV-1 isolates and seem to be used regularly, others have only been identified in single clones of HIV-1 and/or become only active upon mutation of canonical splice sites.…”
Section: Hiv-1 Fusion Proteins Generated By Alternative Splicingmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the canonical splice sites, several studies have reported the presence of alternative or cryptic splice sites in different clades of HIV-1 group M (Purcell and Martin, 1993; Ocwieja et al, 2012; Vega et al, 2016). While some of these sites are conserved among diverse HIV-1 isolates and seem to be used regularly, others have only been identified in single clones of HIV-1 and/or become only active upon mutation of canonical splice sites.…”
Section: Hiv-1 Fusion Proteins Generated By Alternative Splicingmentioning
confidence: 99%
“…They hypothesized that at least one of these two proteins may represent an alternative Tat-Rev fusion product that is expressed if tat1 is fused in frame to rev2 , without any additional env sequences. Notably, comprehensive analyses of mRNA species in HIV-1 infected cells identified several neighboring splice acceptor sites at the 5′ end of rev2/tat2 that introduce a frameshift and may result in the expression of various chimeric Rev1-Tat2 or Tat1-Rev2 proteins (Figure 2, Table 1) (Schwartz et al, 1990a; Purcell and Martin, 1993; Ocwieja et al, 2012; Vega et al, 2016). Although at least some of these splice sites can be found in diverse subtypes of (primary) HIV-1 group M isolates (Vega et al, 2016), the expression of chimeric Tat/Rev proteins and their possible role in viral replication has never been investigated.…”
Section: Hiv-1 Fusion Proteins Generated By Alternative Splicingmentioning
confidence: 99%
See 3 more Smart Citations